Evaluating the effects of work-organizational on musculoskeletal disorder among home tailors - Rozali, Nur Syafiillah; Mohd Nawi, Nur Syazwani (Universiti Utara Malaysia, 2020)
Various studies agreed that sewing machine operators is one of the high-risk group to develop musculoskeletal disorder (MSD). Tailoring involves tedious, highly dreary task like cutting, assembling, pressing and finishing, performed in a sitting position with head bent over the sewing machine and back curved forward. This position is extremely awkward for the body and working like this in a long duration will increases the chance of developing work related MSD. The effects of work-organizational on musculoskeletal disorders were studied on five tailors from Jerantut, Pahang who are working (sewing) at home. From the analysis, there are two activities that contribute the most to musculoskeletal disorder; bending sideways to pick up materials and kneeling down to measure and cut material.